How altruistic alternatives reverse the compromise effect - Amelie Griesoph; Thomas F. Schreiner; Valentyna Melnyk; Holger D. Jänichen (Marketing Letters, 2024)
Brand managers increasingly add altruistic product attributes, such as fair trade or charitable donations, to their products to account for consumers' increasing expectations of altruistic brand behavior. Despite the extensive amount of altruistic product attributes in today's markets, it is unclear how these attributes affect consumer decision-making in different contexts. This paper particularly examines the influence of altruistic product attributes on the compromise effect. Through five experimental studies, we provide pioneering evidence that consumers face general difficulty in accepting trade-offs involving altruistic attributes and that altruistic attributes change the compromise effect substantially. While the well-established compromise effect, predicting a preference for middle options (compromises) over extreme options, holds for trade-offs between utilitarian attributes, it diminishes for altruistic trade-offs. Moreover, the trade-offs between utilitarian and altruistic attributes reverse the compromise effect, i.e., leading to a preference for extreme options. We also demonstrate that impression management moderates this effect.
Keywords: 380; Compromise effect; Altruistic attributes; Utilitarian attributes; Decision-making; Decision difficulty; Impression management